PERENCANAAN PONDASI DANGKAL SUATU GUDANG YANG DITINJAU BERDASARKAN DAYA DUKUNG TANAH DAN TULANGANNYA - Suroyyah, Reza Kholishotul (Jurnal Vokasi Teknik Sipil, 2023)
Foundation planning needs to be considered in building planning in order to achieve a stability and safety. In planning the foundation is influenced by many factors, including the condition of the soil. With different soil conditions, in this case different depths and with the existence of a shallow groundwater table affecting the foundation planning, therefore it is necessary to analyze the soil bearing capacity. In addition, it is also necessary to calculate the required reinforcement according to the foundation to be used.